The catalytic investigation of nanoferrites on the thermal decomposition behavior of AN-based composite solid propellant. (2nd January 2021) - Vara, Jalpa A.; Dave, Pragnesh N.; Chaturvedi, Shalini
Abstract: In this present article, we studied the catalytic efficiency of three different nanoferrites (CuNiF, CoMnF and NiZnF) on the thermal behavior of ammonium nitrate (AN) and composite solid propellants (CSPs) samples. A co-precipitation method was used for synthesized CuNiF, CoMnF and NiZnF nanoparticles and they were characterized by X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). The catalytic efficiency of nanoferrites on thermal behavior of AN and CSPs was investigated by utilizing thermogravimetric-differential scanning calorimetry (TG-DSC) technique. The Flynn wall Ozawa (FWO), Kissinger akahira sunose (KAS) and Starink methods were utilized to determine the activation energies of all AN and CSPs samples. The CoMnF showed good catalytic efficiency on AN and CSPs that reduced the decomposition temperature and activation energy of AN and CSPs; and also increased the burning rate of CSPs.